2019
DOI: 10.1111/desc.12837
|View full text |Cite
|
Sign up to set email alerts
|

Children lose confidence in their potential to “be scientists,” but not in their capacity to “do science”

Abstract: Over the course of middle childhood, children's interest and beliefs about their own capacities for success in science often decline. This pernicious decline is especially evident among underrepresented groups, including girls, members of some racial and ethnic minorities, and children from lower socioeconomic backgrounds. The present research (N = 306, ages 6–11) found that while children lose interest and feelings of efficacy about their potential to “be scientists” across middle childhood, they maintain mor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…Normative expectations about categories, like gender roles, can shape expectations and behavior throughout development, from toy choice (Taylor, 1996) to who gets hired for top leadership positions (Brescoll, Dawson, & Uhlmann, 2010). Beliefs about who is likely to possess certain traits can even have consequences for children's judgments and motivation (Lei, Green, Leslie, & Rhodes, 2019;Liben, Bigler, & Krogh, 2001;Rhodes, Leslie, Yee, & Saunders, 2019). Understanding how normative beliefs about social role categories change across age, and how these beliefs shape categorization and category use, are therefore crucial not only to our understanding of social role concepts, but also to the study of conceptual development in general.…”
Section: Discussionmentioning
confidence: 99%
“…Normative expectations about categories, like gender roles, can shape expectations and behavior throughout development, from toy choice (Taylor, 1996) to who gets hired for top leadership positions (Brescoll, Dawson, & Uhlmann, 2010). Beliefs about who is likely to possess certain traits can even have consequences for children's judgments and motivation (Lei, Green, Leslie, & Rhodes, 2019;Liben, Bigler, & Krogh, 2001;Rhodes, Leslie, Yee, & Saunders, 2019). Understanding how normative beliefs about social role categories change across age, and how these beliefs shape categorization and category use, are therefore crucial not only to our understanding of social role concepts, but also to the study of conceptual development in general.…”
Section: Discussionmentioning
confidence: 99%
“…Normative expectations about categories, like gender roles, can shape expectations and behavior throughout development, from toy choice (Taylor, 1996) to who gets hired for top leadership positions (Brescoll, Dawson, & Ullmann, 2010). Beliefs about who is likely to possess certain traits can even have consequences for children's judgments and motivation (Lei, Green, Leslie, & Rhodes, 2019;Liben, Bigler, & Krogh, 2001;Rhodes, Leslie, Yee, & Saunders, 2019). Understanding how normative beliefs about social role categories change across age, and how these beliefs shape categorization and category use, are therefore crucial not only to our understanding of social role concepts, but also to the study of conceptual development in general.…”
Section: Normative Social Concepts In Early Childhood 17mentioning
confidence: 99%
“…Studies have shown that, while children may lose confidence in their potential to be scientists, they do not lose their ability to do science; this was especially evident in underrepresented groups. 141 As AE progresses, it can help make scientific research more accessible and appealing to everyone, especially those at risk.…”
Section: Potential Impact Of Ae On Materials Science Researchmentioning
confidence: 99%